2020
DOI: 10.1101/2020.11.09.360644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-dependent increase in α-tocopherol and phytosterols in maize leaves exposed to elevated ozone pollution

Abstract: Tropospheric ozone is a major air pollutant that significantly damages crop production around the world. Crop metabolic responses to rising chronic ozone stress have not been well-studied in the field, especially in C4 crops. In this study, we investigated the metabolomic profile of leaves from two diverse maize (Zea mays) inbred lines and the hybrid cross during exposure to season-long elevated ozone (~100 nL L−1) in the field using free air concentration enrichment (FACE) to identify key biochemical response… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…In addition, antioxidants in the apoplast, including ascorbate, glutathione, and phenolic compounds, directly scavenge ROS (Ainsworth, 2017; Grace & Logan, 2000; Wedow et al, 2021a). However, previous studies have failed to demonstrate a clear pattern of correlation between O 3 sensitivity and antioxidant compound levels among diverse species (Betzelberger et al, 2010; Choquette et al, 2020; Li et al, 2016; Wedow et al, 2021b). Furthermore, variation in plant responses to O 3 may also be partly explained by genetic background (Choquette et al, 2019; Sorgini et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, antioxidants in the apoplast, including ascorbate, glutathione, and phenolic compounds, directly scavenge ROS (Ainsworth, 2017; Grace & Logan, 2000; Wedow et al, 2021a). However, previous studies have failed to demonstrate a clear pattern of correlation between O 3 sensitivity and antioxidant compound levels among diverse species (Betzelberger et al, 2010; Choquette et al, 2020; Li et al, 2016; Wedow et al, 2021b). Furthermore, variation in plant responses to O 3 may also be partly explained by genetic background (Choquette et al, 2019; Sorgini et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…This further suggests that C 4 crops may have lower stomatal O 3 uptake than C 3 crops. Nevertheless, previous studies have shown significant impacts of O 3 on maize ( Zea mays ) (Choquette et al, 2019, 2020; Sorgini et al, 2019; Wedow et al, 2021b; Yendrek et al, 2017a, 2017b), switchgrass ( Panicum virgatum ) (Li et al, 2019) and sugarcane (Saccharum spp.) (Moura et al, 2018), but not on sorghum ( Sorghum bicolor L.) (Li et al, 2021) under field conditions, implying the adverse effects of O 3 on plant photosynthesis and productivity vary among C 4 species and genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…So far, only four C 4 crops have been studied for O 3 response using O 3 -FACE facilities (Table 1). Research from SoyFACE showed elevated O 3 concentrations (approximately 100 ppb) significantly reduced leaf photosynthetic capacity in maize (Choquette et al, 2019(Choquette et al, , 2020Sorgini et al, 2019;Wedow et al, 2021b;Yendrek et al, 2017a,b), but had little or no effect on photosynthesis and biomass yield in switchgrass (Li et al, 2019a) and sorghum (Li et al, 2021). These studies also reported considerable genotypic variation in O 3 sensitivity among maize and sorghum lines (Choquette et al, 2019;Li et al, 2021;Yendrek et al, 2017a,b).…”
Section: Lessons Learned From Face Experiments C 3 Versus Cmentioning
confidence: 95%
“…For instance, changes in activity of enzymes involved in ROS metabolism and detoxification (namely catalase [CAT], superoxide dismutase [SOD], and ascorbate peroxidase [APX]) have been found under chronic O 3 exposure in wheat (Feng et al, 2016) and sugarcane (Moura et al, 2018), and these changes were linked to differential photosynthetic and yield sensitivities to O 3 among genotypes. Wedow et al (2021b) investigated differential sensitivity between two inbred maize lines (B73 and Mo17) and the hybrid cross (B73 x Mo17) in relation to the accumulation of defense metabolites in leaf tissue. Senescence was accelerated in the hybrid compared to the inbred lines under elevated [O 3 ] and O 3 -induced reductions in photosynthetic carbon assimilation during grain filling were greater in the hybrid line, leading to significantly greater yield loss.…”
Section: Protection Versus Productivity During O 3 Stressmentioning
confidence: 99%
“…Additionally, studies must look beyond ascorbate and glutathione as other metabolites detoxify the cell during O 3 stress. Secondary metabolites, including α-tocopherol and phytosterols, increased in field-grown maize exposed to season-long chronic O 3 stress [97]. To ensure accurate modeling and improved breeding for O 3 tolerance, the temporal and spatial antioxidant response needs to be resolved, perhaps independently for each species.…”
Section: Biochemical Detoxification Of Omentioning
confidence: 99%